Mechanism of TGIF1 on glycolipid metabolism disorders in mice with type 2 diabetes - Yuchen Li; Li Tao; Shikai Wang; Fuyan Bai; Liping Zheng; Lijun Hou (BMJ Open Diabetes Research & Care)
Introduction Type 2 diabetes (T2D) is a chronic condition characterized by high levels of blood glucose resulting from the inefficiency of insulin. This study aims to explore the mechanism of TGFB-induced factor homeobox 1 (TGIF1) in the glycolipid metabolism of mice with T2D.Research design and methods Mice with T2D were induced by high-fat diet and low-dose streptozotocin (STZ) injection. After TGIF1 was overexpressed in mice with T2D, the weight was monitored. The levels of fasting plasma glucose, fasting serum insulin, triglycerides, total cholesterol, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol were measured. Staining assays were performed to observe liver tissue pathology and lipid accumulation. Liver function and oxidative stress were measured. Palmitic acid (PA)-induced primary hepatocytes were used to establish cell models. After TGIF1 was overexpressed in the cells, cell viability, cellular glucose uptake and consumption, and intracellular glycogen content were detected. The expression of TGIF1, miR-106b-5p, and early growth response 2 (EGR2) was detected and their binding relationships were analyzed. Combined experiments were conducted to validate the mechanism.Results TGIF1 was downregulated in mice with T2D. TGIF1 overexpression reduced hyperglycemia and hyperlipidemia, improved insulin resistance, increased liver glycogen content, and attenuated lipid accumulation and glycolipid metabolism disorders in mice with T2D. TGIF1 was enriched on the miR-106b-5p promoter and promoted miR-106b-5p expression. miR-106b-5p inhibited EGR2 expression. miR-106b-5p inhibition or EGR2 overexpression partially reversed the alleviative effect of TGIF1 overexpression on glycolipid metabolism disorders.Conclusion TGIF1 reduces glycolipid metabolism disorders in mice with T2D through the miR-106b-5p/EGR2 axis.